Pengembangan Media Pembelajaran Video Animasi 3D berbasis Powtoon pada Materi Kesebangunan - Idris, Alya Cahyani; Abrar, Andi Ika Prasasti; Nursalam; Suharti; Baharuddin (Faculty of Tarbiyah and Teacher Training, 2024)
3D animation video learning media is an audiovisual media that can attract students' attention to follow the learning process. This study aimed to determine the development process and characteristics of 3D animation video learning media based on Powtoon that meet the validity, practicality, and effectiveness in mathematics learning. The type of research used is Research and Development (R&D) concerning the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. Based on the study results, validity was obtained in the very valid category. Practicality was obtained based on the results of the teacher response questionnaire in the very good category and the learning implementation sheet in the fully implemented category, from both assessments, the learning media met the practical criteria. Effectiveness was obtained based on the results of the student response questionnaire, which was in the very good category, the assessment of student activities was in the good category, and the learning outcome test was in the high category, so the learning media met the effective criteria. Thus, it is concluded that 3D animation video learning media for similar material is suitable for learning because it can fulfil the three criteria. The implications of this study indicate that using Powtoon-based 3D animated video learning media can improve the quality of mathematics learning, especially in terms of motivation, active participation, and student learning outcomes.